Transplacental transfer of 25-hydroxy-cholecalciferol. Issue 681 (July 1982) - Gupta, M. M.; Kuppuswamy, G.; Subramanian, A. R.
Abstract : Plasma calcium, inorganic phosphorus, alkaline phosphatase, magnesium and 25-hydroxy-cholecalciferol (25-OH-D3) levels were determined on venous blood in 60 Indian mothers during labour. The same analyses were carried out on the cord blood and the infant's venous blood 96 hr after birth. The mean values of plasma calcium, inorganic phosphorus and magnesium were significantly raised in the cord blood compared to those in the maternal blood (calcium and phosphorous P <0·001 and magnesium P <0·01). The mean plasma levels of 25-OH-D3 in the maternal and cord blood were 11·7 ng/ml and 9·6 ng/ml respectively, the cord blood level being about 81% of the maternal. There was a highly significant correlation between these concentrations ( r =0·80, P <0·001). The plasma 25-OH-D3 was subnormal in 12 pregnant mothers at labour and 14 infants. The study highlights the low vitamin D state of Indian pregnant mothers and their newborn infants. The plasma 25-hydroxy-cholecalciferol in pregnancy may reach subnormal levels which are often associated with clinical osteomalacia. This, in turn, adversely affects the vitamin D state of the infant.